FREQUENCY OF HYDATIDOSIS OF CHILDREN AND ADOLESCENTS HOSPITALIZED IN THE NATIONAL CHILD HEALTH INSTITUTE (PERIOD 1996-2005) - Huamán G., Iván (2010)
The objective of the study was to determine the frequency of patients with hydatidosis at the Instituto Nacional de Salud del Niño (INSN), Lima, during the period 1996-2005. Clinical records of 177 patients out of 235 patients diagnosed with hydatidosis were analyzed. The frequency of patients with hydatidosis was 0.21% (235/109 550). The largest number of patients were from Lima department (33.9%, 60/177), followed by Junín and Pasco. The 55.4% (98/177) of patients was male and 50.8% (90/177) of patients were between 5 and 9 years of age. The 44.0% (78/177) of patients suffered pulmonary hydatidosis and 23.2% (41/177) had hepatic hydatidosis. Results indicated that an urban cycle of the diseases would be occurring.